Auditory-Cognitive Training Improves Language Performance in Prelingually Deafened Cochlear Implant Recipients - Ingvalson, Erin M. (2014)
OBJECTIVES: Phonological and working memory skills have been shown to be important for the development of spoken language. Children who use a cochlear implant (CI) show performance deficits relative to normal hearing (NH) children on all constructs: phonological skills, working memory, and spoken language. Given that phonological skills and working memory have been shown to be important for spoken language development in NH children, we hypothesized that training these foundational skills would result in improved spoken language performance in CI-using children. DESIGN: Nineteen prelingually deafened CI-using children aged 4- to 7-years-old participated. All children had been using their implants for at least one year and were matched on pre-implant hearing thresholds, hearing thresholds at study enrollment, and non-verbal IQ. Children were assessed on expressive vocabulary, listening language, spoken language, and composite language. Ten children received four weeks of training on phonological skills including rhyme, sound blending, and sound discrimination and auditory working memory. The remaining nine children continued with their normal classroom activities for four weeks. Language assessments were repeated following the training/control period. RESULTS: Children who received combined phonological-working memory training showed significant gains on expressive and composite language scores. Children who did not receive training showed no significant improvements at post-test. On average, trained children had gain scores of 6.35 points on expressive language and gain scores of 6.15 points whereas the untrained children had test-retest gain scores of 2.89 points for expressive language and 2.56 for composite language. CONCLUSION: Our results suggest that training to improve the phonological and working memory skills in CI-using children may lead to improved language performance.